Effect of Frequency of Self-monitoring Blood Glucose Levels on Glycated Hemoglobin (HbA1c) Levels in Patients with Type 2 Diabetes Mellitus Treated with Oral Anti-diabetic Drugs. - Khan, Sana; Fiaz, Saffa; Anwer, Muhammad Wasim; Jamal, Daniyal Ahmad (Journal of Neonatal Surgery, 2025)
Objectives: To assess the association between rising frequency of self-monitoring the blood glucose (SMBG) and glycated hemoglobin (HbA1c) levels amongst the subjects with type 2 diabetes mellitus who take oral anti-diabetic medications. Research Design: A cross-sectional observational study type with a sample group of high and low-frequency self-monitoring participants are compared to each other. Setting: Fauji Foundation Hospital, Lahore. Participants: Sample size 50 patients aged above 25 years with diabetes mellitus type 2 and exceeding 1 year history, who are taking oral anti-diabetic drugs. Inclusion criteria, such as insulin therapy, pregnancy, end-stage renal disease, blindness, and severe and chronic hepatic disease, were minimized. Interventions: Subjects were divided into two groups based on SMBG assessment as follows: Group A (>3 times/ week) and Group B (<3 times/week). A semi-structured questionnaire was administered to all the participants to capture data concerning their demographic information, information on their clinical characteristics, and their monitoring policies. Main Outcome Measures: The primary outcome is the HbA1c levels. Second outcomes include fasting blood glucose levels, patterns of drug compliance, and demographic harmonization of the frequency of monitoring. Results: A total of 50 patients (28 men) were enrolled, and the mean (SD) age was 58.2 (12.3) years. There were 25 patients in Group A, where the monitoring frequency was frequent (>=3/week), and 25 patients in Group B, where the monitoring frequency was infrequent (<3/week). The mean HbA1c levels of patients in Group A were comparatively low compared to those in Group B (6.4 (0.8)% vs 6.9 (1.1)%, P<0.05; 95% confidence interval of gap -0.8, -0.1). Frequent monitoring was associated with better glycemic control and a higher education level. Conclusion: Regular self-monitoring of blood glucose levels (>=3 times/week) among patients with type 2 diabetes who used oral anti-diabetic medications was found to substantially improve their glycemic levels in terms of the HbA1c readings